Production Cost Analysis at PTPN VII Gunung Dempo Packaging Station using Activity-Based Costing Method - Putri Amro, Alda; Rahmadani Zahra, Carissa; Fitriani, Lailatul; Putri Fadillah, May; Altis Irawan, Tito; Iskandar, Yelita Anggiane; Lusiani, Mirna (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
Production costs consist of components that are directly attached to the product, including direct and indirect costs. In determining production costs such as packaging costs, the usage of the traditional model is not always suitable shown by the possibility of overstated or understated conditions. This study aims to propose the implementation of the Activity-based Costing (ABC) System in calculating the cost of tea packaging and finding the differences with the traditional costing. The data used were based on the case of PTPN VII Gunung Dempo, South Sumatra, Indonesia. The results using the ABC system show that the total cost per unit for BOPF tea products is IDR 34,444.45, for Dust products is IDR 35,629.77, and for Dust II products is IDR 35,629.77. While the traditional system calculation shows that the total cost per unit for BOPF tea products is IDR 61,982.60, for Dust tea products is IDR 61,982.60, and for Dust II tea products is IDR 61,982.60. The strategy that can be applied to avoid possible losses in determining packaging costs due to incorrect cost calculations using the traditional system model is to implement Activity-based Costing.